2018
DOI: 10.1016/j.mib.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic heterogeneity in clonal microbial populations

Abstract: In the past decades, numerous instances of phenotypic diversity were observed in clonal microbial populations, particularly, on the gene expression level. Much less is, however, known about phenotypic differences that occur on the level of metabolism. This is likely explained by the fact that experimental tools probing metabolism of single cells are still at an early stage of development. Here, we review recent exciting discoveries that point out different causes for metabolic heterogeneity within clonal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 81 publications
4
91
0
Order By: Relevance
“…Increasing evidence suggests that individual cells in a population can be metabolically very different (Nikolic et al, 2013;van Heerden et al, 2014;Solopova et al, 2014;Kotte et al, 2015;Takhaveev & Heinemann, 2018). Metabolic heterogeneity has been found, for instance, not only in microbial cultures used for biotechnological processes (Xiao et al, 2016), but also in cells of human tumors (Strickaert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that individual cells in a population can be metabolically very different (Nikolic et al, 2013;van Heerden et al, 2014;Solopova et al, 2014;Kotte et al, 2015;Takhaveev & Heinemann, 2018). Metabolic heterogeneity has been found, for instance, not only in microbial cultures used for biotechnological processes (Xiao et al, 2016), but also in cells of human tumors (Strickaert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here, particularly knowing the flux through glycolysis would be valuable, as this flux has been shown to correlate with highly productive phenotypes (Gupta et al, 2017) and cancer (Pavlova & Thompson, 2016). While nowadays metabolic fluxes can be resolved in ensembles of cells, for instance, by means of 13 C flux analysis (Antoniewicz, 2015), inference of fluxes in individual cells, however, is not possible until today (Takhaveev & Heinemann, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review article by Heins and Weuster‐Botz () has summarized several mechanisms, such as (a) bet‐hedging; (b) noise in gene expression; (c) persistence; (d) bistability, behind population heterogeneity in microbial bioprocesses. Also, recent findings have concluded that stochastic fluctuations in the molecular level can propagate by both regulatory proteins and metabolic reactions and the inherently stochastic cellular metabolism could be a generic source of phenotypic heterogeneity (Kiviet et al, ; Takhaveev & Heinemann, ). For example, Nikolic et al () showed that in clonal bacterial populations such metabolic specialization can be driven by stochastic gene expression, and consequently, large variation in metabolic activities between single cells was found in terms of the assimilation of different sugars (glucose and arabinose).…”
Section: Introductionmentioning
confidence: 99%
“…In particular the determination of steady-state cAMP levels remains difficult using currently available methods, and for this reason many of the functional implications of basal cAMP levels are still under debate 4,[46][47][48] . Finally, it is still unknown whether heterogeneity occurs in single-cell cAMP responses; Cell-to-cell heterogeneity is especially relevant for industrial bioprocessing where glucose-signalling heterogeneity can affect industrial efficiency [49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%